SOSIALISASI PENTINGNYA BER-NPWP UNTUK MENDUKUNG KEGIATAN USAHA DAN TATA CARA PENDAFTARAN NPWP DI DESA LEREP KECAMATAN UNGARAN BARAT KABUPATEN SEMARANG - Setyorini, Christina Tri; Aziz, Abdul; Dewi, Sevita Sari; Apriliantika, Annisa; Sholihah, Siti Mar'atush; Nurmalitasari, Fahmi (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2024)
The village of Lerep is located in the western Ungaran district of Semarang Regency. Through observations of micro, small, and medium enterprises (SMEs) in the village of Lerep, it is known that there are problems related to tax literacy, i.e., there is still a low understanding of the authorities of SMEs about the importance of the Taxpayer Identification Number, both for individuals and for their enterprises. As an attempt to improve understanding, socialization activities were carried out on SMEs perpetrators in Lerep Village with the involvement of 26 participants. The activities consist of two subjects, namely the first, which discusses the importance of NPWP and its registration procedures, and the second, which concerns the preparation of simple financial reports and marketing strategies. The result of this community service activity is a better understanding of the importance of the SMEs, accompanied by a module of guidance for the registration of the Taxpayer Identification Number that can be used by SMEs perpetrators to ensure the survival of their endeavors. Implications of this socialization activity include increased awareness of tax obligations among SMEs owners, which is expected to increase tax compliance as well as the tax contribution of the UMKM sector to economic and social development in Lerep Village and its surroundings.